Hempseeds (Cannabis spp.) as a source of functional food ingredients, prebiotics and phytosterols - Grigoriev, Sergei; Illarionova, Ksenia; Shelenga, Tatiana (Agricultural and Food Science, 2020)
The history of agriculture gives evidence that hemp have been cultivated by farmers near the northern border of agriculture for seed and oil. Nowadays, hemp is a focus of interest as a source of prebiotics and functional food ingredients. This study was aimed at the evaluation of physiologically active metabolomic compounds in the seed of thirty-three Cannabis spp. accessions, representing industrial dual-purpose (fiber and seed), universal, breeding materials used for food, ruderal and recreational landraces grown the Northwest of Russia. Amounts of polyunsaturated fatty acids, polysaccharides, polyhydric alcohols, phytosterols and phytol in seeds were measured. The maximum of linoleic acid reached 4379.41 mg 100 g-1, linolenic acid 427.72, oleic acid 1711.19, polysaccharides 13111.28, polyhydric alcohols 2138.38, and sitosterol 79.36. Ruderal hemp was found abundant in phytol (3.46 mg 100 g-1). The food seed/oil material contained the maximum of campesterol and sitosterol. The evaluated hemp accessions may be used as sources of physiologically active and safe ingredients of healthy food and phytosterols as well as in breeding programs to develop hempseed cultivars.